2022
DOI: 10.1371/journal.pone.0265991
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation of two begomovirus acquired and inoculated by different cryptic species of whitefly, Bemisia tabaci in Okra

Abstract: The whitefly, B.tabaci is a major pest of agricultural crops which transmits begomovirus in a species-specific manner. Yellow vein mosaic disease (YVMD) and okra leaf curl disease (OLCD) caused by distinct begomovirus are a major limitation to production of okra in India. In this framework the present investigation reports, for the first time, comparative study of begomovirus species viz. yellow vein mosaic virus (YVMV) and okra enation leaf curl virus (OELCuV) ingested and egested by two cryptic species (Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The Indian region exhibits an enormous diversity of B. tabaci with the presence of 10 cryptic species among the 46 species recorded so far (Rehman et al, 2021 ). The vast array of genetic groups not only specialize in host plant preference, but also exhibit a diverse dispersal pattern and differential response to pesticides (Pashley et al, 1992 ; Adamczyk et al, 1997 ; Barman et al, 2022 ). In this regard, precise assessment of the genetic identity and insecticide resistance properties is imperative for the development of control strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Indian region exhibits an enormous diversity of B. tabaci with the presence of 10 cryptic species among the 46 species recorded so far (Rehman et al, 2021 ). The vast array of genetic groups not only specialize in host plant preference, but also exhibit a diverse dispersal pattern and differential response to pesticides (Pashley et al, 1992 ; Adamczyk et al, 1997 ; Barman et al, 2022 ). In this regard, precise assessment of the genetic identity and insecticide resistance properties is imperative for the development of control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…They inflict damage to plants directly and as a vector of several hundred viruses, with a majority (>320 species) of them belonging to the genus Begomovirus and other economically important viruses belonging to the genera Ipomovirus, Carlavirus, Crinivirus, Torradovirus, and Polerovirus (Jones, 2003 ; Mugerwa et al, 2021 ). Whitefly is composed of a complex group of genetically distinct species and/or biotypes that differ substantively by host plant preference, virus transmitting ability, and insecticide resistance (De Barro et al, 2011 ; Barman et al, 2022 ). It is listed as one of the top 100 dreadful alien invasive species due to its virus transmission ability and wide host adaptability (Lowe et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The spread of the virus strictly depends on the feeding time of the insect. Very recently it has been reported that white y can inoculate 4.19E + 11 number of chilli leaf curl virus during a 5 min of feeding [28] whereas in Okra 24 hours of feeding time by white y has been shown to acquire only 10 4 to 10 5 copies of virus [29]. In sub-Himalayan terai region chilli is grown in the month of March-April which overlaps with high surge of white y population resulting in frequent begomoviral infection.…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, B. tabaci is extremely polyphagous, being able to feed on more than 1000 plant species; however, recent studies have revealed that the species of the complex differ greatly in their degree of polyphagy [90,91]. Also, in the past few years, increasing numbers of reports have shown that species of the B. tabaci complex differ in their capacity to transmit certain begomoviruses, and that a single B. tabaci species can differentially transmit specific begomoviruses [92,93].…”
Section: To Seed or Not To Seed: The Open Question Of Begomovirus See...mentioning
confidence: 99%